2003
DOI: 10.1097/01.lab.0000101701.87433.c5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool for Detecting Amyloid Deposits in Systemic Amyloidosis In Vitro and In Vivo

Abstract: SUMMARY:We synthesized (trans,trans)-1-bromo-2,5-bis-(3-hydroxycarbonyl-4-hydroxy)styrylbenzene (BSB) and used this compound to detect amyloid fibrils in autopsy and biopsy samples from patients with localized amyloidosis, such as familial prion disease, and systemic amyloidosis, such as familial amyloidotic polyneuropathy, amyloid A (AA) amyloidosis, light chain (AL) amyloidosis, and dialysis-related amyloidosis. BSB showed reactions in all Congo red-positive and immunoreactive regions of the samples examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Although amyloid deposits are usually identified by means of CR staining, our histopathological studies showed that venous EFEMP1 amyloid deposits had faint CR staining. In contrast, these venous EFEMP1 amyloid deposits were confirmed by electron microscopy and were clearly detected by FSB fluorescent staining, which is reportedly a more sensitive method than CR staining to detect various kinds of amyloid deposits . We should note, therefore, that CR staining may be not sufficient to detect venous EFEMP1 amyloid deposits and may sometimes lead to misdiagnosis of EFEMP1 amyloidosis, so more sensitive methods, such as FSB staining and immunohistochemical staining, are preferred for a more accurate diagnosis of venous EFEMP1 amyloidosis.…”
Section: Discussionmentioning
confidence: 91%
“…Although amyloid deposits are usually identified by means of CR staining, our histopathological studies showed that venous EFEMP1 amyloid deposits had faint CR staining. In contrast, these venous EFEMP1 amyloid deposits were confirmed by electron microscopy and were clearly detected by FSB fluorescent staining, which is reportedly a more sensitive method than CR staining to detect various kinds of amyloid deposits . We should note, therefore, that CR staining may be not sufficient to detect venous EFEMP1 amyloid deposits and may sometimes lead to misdiagnosis of EFEMP1 amyloidosis, so more sensitive methods, such as FSB staining and immunohistochemical staining, are preferred for a more accurate diagnosis of venous EFEMP1 amyloidosis.…”
Section: Discussionmentioning
confidence: 91%
“…A fluorescent derivative of Congo Red, (trans, trans)-1-bromo-2,5-bis-(3-hydroxycarbonyl-4-hydroxy)styrylbenzene (BSB), has also been employed for the detection of amyloid deposits in tissue sections [19]. With an emission maximum of 520 nm, this probe offers improved performance with respect to the avoidance of background associated with intrinsic and fixative-induced autofluorescence in cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with small amyloid deposits, repeated biopsies should be required to confirm the diagnosis. In addition to the commonly used Congo red staining, (E,E)-1-bromo-2,5-bis-(3-hydroxycarbonyl-4-hydroxy) styrylbenzene (BSB) and (E,E)-1-fluoro-2,5-bis-(3-hydroxycarbonyl-4-hydroxy) styrylbenzene (FSB) can be employed to detect a small amount of amyloid deposits in biopsy specimens, because these two chemical agents bind to amyloid fibrils more strongly than Congo red [49,50].…”
Section: Histopathological Analysesmentioning
confidence: 99%